THE ANALYSIS OF CUSTOMER SATISFACTION OF CORNED PRONAS PRODUCT OF PT CIP, DENPASAR, BALI - Sukardi dan Chodilis Chandrawatisma (Department of Agroindustrial Technology, Bogor Agricultural University, 2008)
ABSTRACTPT Canning Indonesian Products (PT CIP), formed by Japanese Government in 1942, is one of the oldest canned food companies in Indonesia. Its main product is known as PRONAS. A fierce competition like of today in food industry imposes PT CIP to increase and improve the values of its PRONAS attributes.The purposes of this research are to: (1) identify the corned PRONAS customer characteristics, (2) determine customer’s decision process to consume corned PRONAS, (3) determine customer’s response to the attributes of corned PRONAS, (4) analyze customer satisfaction level of corned PRONAS.By using Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) method, the results of this research show that corned PRONAS is a trans gender food with respondents characteristic dominated by age of 25 – 34 year old, most of them are bachelor and work for private sector. Most of the respondents are of middle and top class society, their buying decision is based on flavor, they always planned ahead before purchasing, most of them are self willingness, and their preference is corned of the size of 198 grams. The IPA analysis shows that the core priority to improve the products includes smell, product ingredients, flavor in accordance with price, color, the volume size, and accessibility. The products should be maintained in their attributes of expiration date, halal status, product permit from Department of Health, customer service information, and taste. The products are acceptable in terms of price, packaging design, packaging practicallity, prestige, and consumed by many people. The study recommends marketing strategy plan for the company based on CSI and IPA analyses.Keywords : Corned, Customer Satisfaction, Importance Performance Analysis, Customer Satisfaction Index.